Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1111/pbi.14217
|View full text |Cite
|
Sign up to set email alerts
|

EARLY FLOWERING is a dominant gain‐of‐function allele of FANTASTIC FOUR 1/2c that promotes early flowering in tomato

Dedi Zhang,
Guo Ai,
Kangna Ji
et al.

Abstract: SummaryFlowering time, an important factor in plant adaptability and genetic improvement, is regulated by various genes in tomato (Solanum lycopersicum). In this study, we characterized a tomato mutant, EARLY FLOWERING (EF), that developed flowers much earlier than its parental control. EF is a dominant gain‐of‐function allele with a T‐DNA inserted 139 bp downstream of the stop codon of FANTASTIC FOUR 1/2c (FAF1/2c). The transcript of SlFAF1/2c was at elevated levels in the EF mutant. Overexpressing SlFAF1/2c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…SNPs with default r 2 values greater than 0.5 were considered for haplotype block estimation. The R package geneHapR was used for haplotype statistics [ 99 ]. The genes underlying the haplotype blocks were retrieved from the Heinz 1706 SL4.0 tomato reference genome [ 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…SNPs with default r 2 values greater than 0.5 were considered for haplotype block estimation. The R package geneHapR was used for haplotype statistics [ 99 ]. The genes underlying the haplotype blocks were retrieved from the Heinz 1706 SL4.0 tomato reference genome [ 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that MBP21 is involved in the ethylene and auxin regulatory pathway of sepal development [58]. It is also noted that one of the FANTASTIC FOUR family members, FAF1/2c reduces the stability of the COP9 signalosome, thereby regulating the expression of SFT and J [59].…”
Section: Meristem Transitionmentioning
confidence: 99%